A Quest for the Essence of Human Enhancement - Xuan JIANG (Yixue yu zhexue)
Human enhancement refers to the practical operation and application of relevant technologies on human beings (including the physiological, cognitive, emotional and willpower dimensions), and thereby extending, replacing or updating all aspects of the human body, such as intelligence, physical strength and appearance. It can be categorized along three dimensions, namely, the specific domains it targets, the forms or modalities it assumes, and the ways in which the technologies are embedded in society and everyday life. The implementation of such technologies must be guided by clear ethical boundaries and continuously adapted within dynamic and pluralistic socio-temporal contexts. In technological enhancement, loyalty to humanity always takes precedence over innovation in technological means. It is essential to pursue a "pro-subject" approach to enhancement, and prioritizes human-centered values over technology-driven imperatives.